On the use of in-situ piezoelectric sensors for the manufacturing and structural health monitoring of polymer-matrix composites: A literature review. (1st May 2019) - Tuloup, C.; Harizi, W.; Aboura, Z.; Meyer, Y.; Khellil, K.; Lachat, R.
Abstract: This article aims to provide a general overview of what has been achieved recently in the scientific community on the manufacturing monitoring and structural health monitoring of polymer-matrix composites (PMC) using in-situ piezoelectric sensors. Some industrial applications with the underlying issues and potential solutions will finally be discussed in the concluding section.